IMPLEMENTASI PENDIDIKAN KARAKTER DI MADRASAH IBTIDAIYAH: STUDI KASUS DI MIN 13 PIDIE JAYA - Muhammad Daniel; Muhammad Shofwan Hadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Character education has long been an integral part of Indonesian society. Various efforts have been made to develop character education in different forms and names. Character education encompasses basic moral values such as caring, honesty, fairness, responsibility, and respect for oneself and others. In the Era of Society 5.0, education plays a crucial role in preparing quality human resources for national advancement. Character education is expected to significantly contribute to shaping students' good character, especially in elementary schools like MIN 13 Pidie Jaya.This study explores the implementation of character education at MIN 13 Pidie Jaya and identifies factors that support and hinder its implementation. A descriptive qualitative approach is used to accurately depict reality through data collection techniques such as in-depth interviews and documentation. The results show that although most students exhibit good character, some students still lack discipline. The implementation of character education is carried out through various activities such as the application of the 5S principles (smile, greeting, salute, politeness, and courtesy), joint prayers, and timely prayers. Character values such as honesty, responsibility, and environmental care are instilled through daily activities at school. Challenges faced in the implementation of character education include a lack of parental attention and limited interaction between teachers and students. Strategies to overcome these challenges involve better coordination between teachers and parents and the consistent application of approaches in character building. The findings of this study are expected to be used as guidelines for schools in developing effective curricula and learning processes in character education.